The General Education Curriculum in the Philippines: A Policy Analysis - Asio, John Mark; Mendoza, Kristin Joy; Soriano, Imelda (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Due to the fast pace changes and impact of globalization and technological advancement, this is a significant challenge to the educational system. More importantly, the students, the faculty, the institution, the school administration, and the stakeholders have something to think over. Internationalizing the curriculum in the local context is a predicament that the government must address for students to be globally competitive and ready for the challenges of tomorrow. This particular paper analyzed the Philippine General Education Curriculum (GEC). The analysis of this paper resulted in two policy options which provided a comprehensive discussion regarding the ramifications of implementing the new general education curriculum in higher education institutions. Afterward, the paper also shared a SWOT and stakeholders' analysis to provide practical ideas and perspectives for school administrators to consider timely decision-making and school management. Finally, this paper offered some relevant recommendations for future references.